Human-AI Collaboration in Telemedicine and Knowledge Security A Review of Emerging Research Trends - Mohammed Ahmed Alhebbi; Ibrahiem M. M. El Emary (International Journal for Applied Information Management, 2026)
Telemedicine has fundamentally transformed healthcare delivery by enabling remote consultations, diagnoses, and follow-ups, thereby enhancing accessibility and efficiency. Nevertheless, this transformation poses critical challenges related to data security, confidentiality, and the protection of knowledge exchange. This paper seeks to review the literature on knowledge security and its relationship with telemedicine within healthcare organizations. The paper summarizes trends of knowledge security and telemedicine, underscores their interconnections, and traces their evolution over time. It also reviewed the historical development of both concepts, examined them jointly and separately, and addressed their associated notions. Moreover, the study reviewed conferences and scientific societies that engaged with the topic, as well as research interests in the topic and their progression within contemporary intellectual production. Finally, a digital indicator was employed to trace the terminology related to the topic. The study used a descriptive–analytical method, which involved consulting the literature including research papers, articles, and books and subjecting it to both descriptive and analytical examination. This approach was applied to review the key terminology relevant to the topic and to extract related findings and implications. The study concluded from the literature that research interests have addressed knowledge security and information security on the one hand, and telemedicine on the other; however, these domains diverged in their approaches and variables. Furthermore, to the best of the researcher’s knowledge, this literature represents the first contribution in Arabic to link knowledge security with telemedicine explicitly. The researcher intends to expand on this connection in future work to make a distinctive contribution to intellectual production in this field.